Zelfportret. - Hof ter Nederloo, Sint-Pieters-Leeuw (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1987)
Bervoets, Fred ; Bilquin, Jean ; Burssens, Jan De Bruyne, Dees ; De Vuyst, Gaspard ; Frimout, Cyr ; Gobert, Paul ; Landuyt, Octave ; Minnaert, Frans ; Raveel, Roger ; Slabbinck, Rik ; Schuppisser, Peter ; Snauwaert, Jef ; Somville, Roger ; Szymkowicz, Charles ; Timper, Paul ; Van Herreweghen, Anne ; Van Riet, Jan ; Van Schuylenbergh, André ; Vermeersch, José ; Vermeersch, Rik ; Vervisch, Godfried
Zelfportret, Nederloo, Sint-Pieters-Leeuw, 27 november 1987 - 10 januari 1988
boek